“Real-World” Evaluation of Lipid Oxidation Products and Trace Metals in French Fries From Two Chain Fast-Food Restaurants - Le Gresley, Adam; Ampem, Gilbert; De Mars, Simon; Grootveld, Martin; Naughton, Declan P. (Frontiers in Nutrition, 2021)
The differences in lipid oxidation product and heavy metal concentrations of French fry samples found between two fast-food restaurants in the UK were investigated using high- resolution proton nuclear magnetic resonance (1H NMR) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analyses of extracts derived therefrom, respectively. Over the course of 3 days and 3 different diurnal time periods, samples of French fries (FFs) were analysed, and comparisons of the different oil extraction methods were made for the two global chain fast-food restaurants were undertaken. The magnitude of concentrations of LOPs extracted from FFs is discussed. Significant differences between (E,E)-2,4-alkadienals, E-2-alkenals, aluminium and iron levels between samples from the two restaurants are also reported. Higher levels of redox-active metal ions found did not correlate with higher levels of LOPs in these samples.